Proton affinity and gas-phase basicity of pyrogallol and phloroglucinol: a computational study. Issue 1 (4th February 2021) - Mayhan, Collin M.; Kumari, Harshita; Maddalena, Julia M.; Borgmeyer, Gabriel N.; Deakyne, Carol A.
Abstract: We report the proton affinities (PAs) and gas-phase basicities (GBs) of pyrogallol (1, 2, 3-trihydroxybenzene) and phloroglucinol (1, 3, 5-trihydroxybenzene), as determined by high level quantum chemical calculations and a series of isodesmic proton transfer reactions. These yet unmeasured values have relevance to release of active species from nanocarriers derived from the calixarene family of macrocycles. The PAs and GBs obtained for these two trihydroxybenzene isomers are compared and contrasted with those obtained previously for the third isomer, hydroxyquinol (1, 2, 4-trihydroxybenzene). Preferred protonation sites and relative thermochemical values are analyzed in terms of electron delocalization effects and the consequent disruption of intramolecular hydrogen bonding. Graphical Abstract: